Differences in Relational Distress Following RE Intervention for Low-Income Couples With or Without Chronic Illness. (2nd January 2022) - Daire, Andrew P.; Tucker, Kelsee; Wheeler, Naomi J.; Liu, Xun; Williams, Brooke; Regal, Rachel A.; Peoples, Taylar; Moumouris, Teddy
Abstract: With a sample of 2, 118 largely low-income, ethnic minority individuals with and without chronic illness (CI), this study examines couple-oriented relationship education (RE) on emotional distress levels. We applied a correlational research design to examine dyadic changes in distress following a couple RE intervention with a one-group pretest-posttest design. Female participants reported higher relationship distress at baseline. Both females and males showed significant improvement in distress post-RE intervention (Wilks' λ =.93, F (1, 669) = 79.49, p < .001, η 2 = .08); women showed greater improvements at the end of the RE intervention, despite posttest relational distress still being greater than men. The CI group did not benefit more than the non-CI group suggesting further investigation regarding changes in distress post-RE for couples with CI. Counselors may find couple-oriented RE intervention useful to promote relational health in those with CI or as part of a holistic health intervention.